A Qualitative Study of Sleep–Wake Disturbance Among Veterans With Post–Acute Moderate to Severe Traumatic Brain Injury. Issue 2 (March 2016) - Matthews, Ellyn E.; Signoracci, Gina M.; Stearns-Yoder, Kelly; Brenner, Lisa A.
Abstract : Objective: Examine sleep-wake disturbance (SWD) characteristics, factors, consequences, and management strategies from the perspective of veterans with chronic stage, moderate/severe traumatic brain injury (TBI). Setting: VA Medical Center, Rocky Mountain. US Participants: Nineteen male veterans with post–acute TBI and SWD in the VA Health Administration. Design: Qualitative descriptive. Measures: Semistructured interviews, Ohio State University TBI-Identification Method, Insomnia Severity Index. Results: Two main dimensions emerged: " Messed up sleep " and Surviving and Managing SWD. Sleep-wake disturbance has long-term multidimensional features, etiology, consequences, and practice implications. Although SWD may not be consistently discussed with providers, the problem appears to be pervasive in many aspects of the lives of the informants. Difficulty falling asleep, frequent awakenings, and poor sleep quality were common symptoms that were described as intrusive, isolating, and difficult to self-manage. Veterans discussed a host of physical symptoms, mental health issues, environmental, and behavioral factors that contributed to SWD. Medications, sleep apnea treatment, and self-imposed isolation were frequent management strategies. Veterans expressed a willingness to try new approaches and work with providers. Conclusion: Sleep-wake disturbance among veterans with chronic stage TBI is a multidimensional phenomenon with interplay between comorbidities, contributing factors, effects on functioning, and sleep management strategies. Implications for practice include early and routine evaluation, monitoring, and treatment of SWD. Research is needed to test interventions that address SWD and common TBI comorbidities.